PENGARUH SISTEM PENILAIAN KINERJA TERHADAP KINERJA PNS SATUAN KERJA PERANGKAT DAERAH KOTA BANDUNG DENGAN CONTRACTIBILITY SEBAGAI VARIABEL MODERATING - Nunik Lestari Dewi; Mathius Tandiontong; Selma Aghnia Vira (Soso-Q : Jurnal Manajemen, 2018)
This study aims to determine the effect of performance appraisal system on the performance of civil servants Satuan Kerja Kota Bandung with contractibility as a moderating variable. Performance appraisal system in this research is divided into two variables: performance appraisal system oriented incentif / reward and performance appraisal system that oriented exploration. While the moderating variable is contractibility (performance agreement).The results showed that there is influence of performance appraisal system oriented incentives / rewards on the performance of civil servants SKPD Bandung of 75.2%. In addition, there is also the influence of exploration-oriented performance appraisal system on the performance of civil servants SKPD Bandung of 56.2%. The existence of the contractibility variable / performance agreement will strengthen the direct correlation of the independent variable to the dependent variable, so the result shows that there is influence of performance appraisal system oriented incentive / reward to the performance of civil servant SKPD Bandung with variable contractibility / performance agreement as moderating variable and there influence of performance appraisal system oriented exploration on the performance of civil servants SKPD Bandung with variable contractibility / performance agreement as a moderating variable.Keywords: incentive / reward oriented performance appraisal system, exploration-oriented performance appraisal system, contractibility (performance agreement), civil servant performance.